Rational Design of Photothermal and Anti-Bacterial Foam With Macroporous Structure for Efficient Desalination of Water - Wang, Zhifen; Niu, Jin; Wang, Juanxia; Zhang, Yucang; Wu, Guoqiang; Liu, Xiaoyun; Liu, Qun (Frontiers in Chemistry, 2022)
With the environmental deterioration and the rise in demand for sustainability, the lack of freshwater resources has emerged as a global concern. To address this issue, the desalination of water using solar evaporation is centered on as a promising approach. In this study, we designed a light and photothermal liquefied-chitin-based polyurethane foam to achieve efficient water evaporation benefiting from their powerful solar spectral absorption, low thermal conductivity, quick transportation of water, hierarchically porous structures, and anti-biofouling natures. Moreover, because of the introduction of nano-silver, the newly developed foam exhibits considerable antibacterial ability and improved photothermal performance. Notably, the low thermal conductivity of the foam can reduce the loss of absorbed solar heat, whereas its large porous structure provides a smooth water transport channel. More importantly, with the assistance of heat, polyacrylamide hydrogels adhering along with the pores rapidly absorb and desorb water molecules, promoting the evaporation of water and improving solar energy conversion efficiency. Ultimately, under irradiation by one sunlight, the proposed material demonstrated a water evaporation rate and solar photothermal conversion efficiency of 2.44 kg m−2 h−1 and 153.2%, respectively.